2013
DOI: 10.3390/ijerph10062500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electronic Cigarette Use (Vaping) Topography and Estimation of Liquid Consumption: Implications for Research Protocol Standards Definition and for Public Health Authorities’ Regulation

Abstract: Background: Although millions of people are using electronic cigarettes (ECs) and research on this topic has intensified in recent years, the pattern of EC use has not been systematically studied. Additionally, no comparative measure of exposure and nicotine delivery between EC and tobacco cigarette or nicotine replacement therapy (NRTs) has been established. This is important, especially in the context of the proposal for a new Tobacco Product Directive issued by the European Commission. Methods: A second gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
243
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(269 citation statements)
references
References 28 publications
13
243
3
5
Order By: Relevance
“…A 15‐minute break between the 2 exposure sessions was given so that the animals could access fresh air, food, and water. The puff duration was 3 seconds, puff interval 1 minute, and the puff volume was 50 mL, all of which mimics real‐life exposure scenarios 24, 25, 26, 27, 28, 29, 30, 31, 32, 33. As for the controls or control mice, they were matched in terms of age and sex (ie, 10‐week‐old males), and were exposed to clean air.…”
Section: Methodsmentioning
confidence: 99%
“…A 15‐minute break between the 2 exposure sessions was given so that the animals could access fresh air, food, and water. The puff duration was 3 seconds, puff interval 1 minute, and the puff volume was 50 mL, all of which mimics real‐life exposure scenarios 24, 25, 26, 27, 28, 29, 30, 31, 32, 33. As for the controls or control mice, they were matched in terms of age and sex (ie, 10‐week‐old males), and were exposed to clean air.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were instructed to take ten puffs each of three-second duration with a thirtysecond inter-puff interval (IPI). The original intention was to use a longer four second puff duration 8 (as recommended by [30]), however, during a pilot study it became evident that the four-second puff duration was too long for the cigalike device, producing over-heating and coughing. Consequently, puff length was reduced to three seconds for both conditions.…”
Section: Phasementioning
confidence: 99%
“…Surveys of dedicated EC users (which were all former smokers) have shown that high nicotine levels are important especially for the initiation of EC use. 3,4 Although nicotine delivery to the aerosol can be similar or higher than tobacco cigarettes, 5,6 clinical studies of EC use have shown that the nicotine absorption potential is significantly lower compared with tobacco cigarettes, even when new generation devices are used. 7 This is mostly attributed to the low speed of nicotine absorption, and clearly indicates that nicotine intoxication is highly unlikely when ECs are used as intended.…”
Section: Nicotine Delivery From Ecsmentioning
confidence: 99%
“…There is already the example of regulatory decisions by the European Union, which defined an upper limit of 20 mg/ml nicotine concentration in EC liquids (http:// ec.europa.eu/health/tobacco/docs/dir_201440_en.pdf) based on information about potential nicotine delivery to the aerosol. 6 They failed to recognize that both effectiveness and abuse liability are determined by nicotine absorption (speed and amount delivered to the blood stream) rather than nicotine delivery to the aerosol. As a result, it is possible that such a restriction could exclude some smokers from effectively using ECs as smoking substitutes.…”
Section: Is There a Need To Regulate Nicotine Flux In Ecs?mentioning
confidence: 99%